Multiarray cell stretching platform for high-magnification real-time imaging - Huang, Yuli; Nguyen, Nam Trung; Lok, Khoi Seng; Lee, Peter Peng Foo; Su, Maohan; Wu, Min; Kocgozlu, Leyla; Ladoux, Benoît (Nanomedicine, 2013)
Aim: This article reports the development of a multiarray microchip with real-time imaging capability to apply mechanical strains onto monolayered cell cultures. Materials & methods: Cells were cultured on an 8-μ thick membrane that was positioned in the microscope focal plane throughout the stretching process. Each stretching unit was assembled from three elastomeric layers and a glass coverslip. A programmable pneumatic control system was developed to actuate this platform. Multiple stretching experiments were conducted with various cell lines. Results: The platform provides a maximum uniform strain of 69%. Acute and long-term cell morphological changes were observed. The supreme imaging capability was verified by real-time imaging of transfected COS-7 stretching and poststretching imaging of immunofluorescence- stained PTK2. Conclusion: The platform reported here is a powerful tool for studying mechanically induced physiological changes in cells. Such a device could be used in tissue regeneration for maintaining essential cell growth conditions. © 2013 Future Medicine Ltd.
CRIS-Team Scopus Importer:2024-02-19
Keywords: BioMEMS; cyclic cell stretching; high magnification; mechanobiology; microfluidics; pneumatic actuation; polymeric micromachining